UNDERSTANDING HEALTH SEEKING BEHAVIOR OF HEALTH CARE PROFESSIONALS IN TERTIARY CARE HOSPITALS IN PAKISTAN - Bana, Shazia; Yakoob, Javed; Jivany, Nourin; Faisal, Asima; Jawed, Humeira; Awan, Safia (Journal of Ayub Medical College Abbottabad, 2016)
Background: Health seeking behaviour refers to the behaviour of people towards seeking their own health through provided health services. The medical professionals are at a higher risk of avoiding health seeking behaviour because they believe they are aware of the diseases and their symptoms as well as the pharmaceutical management of the disease. The aim of this study was to understand the healthcare seeking behaviour of nurses and doctors as well as the factors affecting it in hospitals of a major city in a developing country. Methods: A cross-sectional study was designed and a self-report questionnaire was distributed to healthcare workers at four tertiary care hospitals from July, 2012 to December, 2014. A total of 1015 participants responded. There were 234 (23%) doctors, 664 (65%) nurses, 60 (6%) pharmacist and 57 (6%) paramedical staff. Results: The doctors 194 (83%) had a greater access to medical facilities compared to nurses 278 (42%) (p<0.001). Doctors 176 (75%) compared to nurses 262 (39%) were utilizing healthcare service more often (p<0.001). Majority of the nurses 494 (74%) never visited a doctor for any complaint over a period of one year compared to doctors 132 (56%) (p=0.002). Doctors 234 (100%) and nurses 662 (99.7%) equally self -medicated themselves (p=0.401). Nurses 134 (20%) were less aware of the organization policies offered for employees ill-health compared to doctors 102 (44%) (p<0.001). Nurses 530 (80%) were also less aware of the significance of regular health check-ups compared to doctor 234(100%) (p<0.001). Conclusions: Among the healthcare workers, doctors have greater access to healthcare facilities. Majority of nurses do not seek healthcare when they get sick. Self-medication is common in both groups. Keywords: Healthcare professionals, health seeking behaviour, self-medication, over the counter medications